Asal-Usul, Konsep dan Kontestasi Wacana Islam Wasatiyah di Indonesia - Najib, Muhammad Ainun; Fata, Ahmad Khoirul (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2019)
by the spread of religious extremism, Islamic discourse of Wasatiyah emerged. A discourse of Islamic origin that originated from the idea of a Malaysian intellectuals, Mohammad Hashim Kamali.  Islam Wasati{yah is the second Islamic discourse imported from Malaysia after Islam H{ad{a>ri’s Abdullah Ahmad Badawi. Islam Wasatiyah tries to present a moderate and tolerant Islamic character based on the values embodied in Islam. This article seeks to answer three questions. First, how did the historical flow of Islam Wasatiyah appear in Indoensai. Second, the conceptual range of Islamic Wasatiyah developed by Indonesian religious and Muslim scholars. Third, the contestation of Islamic discourse Wasatiyah with other discourse.  In this paper it is found that the current support base will be scrathed by the discourse itself.  Keywords:  Moderation, Extremism, Islam Wasatiyah, Islam Nusantara, Islam Berkemajuan   Abstrak Seiring merebaknya ekstrimisme keagamaan, wacana Islam Wasatiyah muncul. Sebuah wacana keislaman yang berasal dari gagasan seorang intelektual Malaysia, Mohammad Hashim Kamali.  Islam Wasatiyah merupakan wacana keislaman kedua yang diimpor dari Malaysia setelah Islam H{ad{a>rinya Abdullah Ahmad Badawi. Islam Wasatiyah mencoba menghadirkan watak Islam yang moderat dan toleran berdasarkan nilai-nilai yang terkandung dalam Islam. Artikel ini berupaya menjawab tiga pertanyaan. Pertama, bagaimana alur historis Islam wasatiyah muncul di Indoensai. Kedua, ragam konseptual Islam wasatiyah yang dikembangkan oleh organisasi keagamaan dan cendekiawan Muslim Indonesia. Ketiga, kontestasi wacana Islam wasatiyah dengan wacana lain.  Dalam tulisan ini ditemukan bahwa basis dukungan yang massif akan menggarustamakan wacana itu sendiri.   Kata Kunci: Moderasi, Ekstrimisme, Islam Wasatiyah, Islam Nusantara, Islam Berkemajuan